Potential outcomes of interpersonal violence for women`s artistic gymnasts: a qualitative analysis - Barker-Ruchti, N. (British Journal of Sports Medicine, 2025)
Objective This study aimed to identify, map and provide insight into the potential outcomes former elite-level women`s gymnasts associate with their history of interpersonal violence (IV).